2021
DOI: 10.1101/2021.04.02.438265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex differences in behavioral and brainstem transcriptomic neuroadaptations following neonatal opioid exposure in outbred mice

Abstract: The opioid epidemic led to an increase in the number of Neonatal Opioid Withdrawal Syndrome (NOWS) cases in infants born to opioid-dependent mothers. Hallmark features of NOWS include weight loss, severe irritability, respiratory problems, and sleep fragmentation. Mouse models provide an opportunity to identify brain mechanisms that contribute to NOWS. Neonatal outbred Swiss Webster Cartworth Farms White (CFW) mice were administered morphine (15mg/kg, s.c.) twice daily for postnatal days (P) 1-14, an approxima… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Similar to our results, one study found that offspring from oxycodone-exposed dams have higher frequency USVs than control offspring (Zanni et al, 2021). Another study also found that neonate offspring injected with morphine from PND 1 – 14 had increased USV frequency parameters (Borrelli et al, 2021). Various studies and reviews have focused on understanding vocalizations and changes in their acoustic parameters, including how upward shifts in frequency modulation is usually associated with an increase in infant distress (Brudzynski, 2015; Castellucci, Calbick, & McCormick, 2019; Esposito, Nakazawa, Venuti, & Bornstein, 2013; Hahn & Lavooy, 2005; Kromkhun et al, 2013; Lingle, Wyman, Kotrba, Teichroeb, & Romanow, 2012; Parga et al, 2020; Wasz-Höckert, Michelsson, & Lind, 1985).…”
Section: Discussionmentioning
confidence: 93%
“…Similar to our results, one study found that offspring from oxycodone-exposed dams have higher frequency USVs than control offspring (Zanni et al, 2021). Another study also found that neonate offspring injected with morphine from PND 1 – 14 had increased USV frequency parameters (Borrelli et al, 2021). Various studies and reviews have focused on understanding vocalizations and changes in their acoustic parameters, including how upward shifts in frequency modulation is usually associated with an increase in infant distress (Brudzynski, 2015; Castellucci, Calbick, & McCormick, 2019; Esposito, Nakazawa, Venuti, & Bornstein, 2013; Hahn & Lavooy, 2005; Kromkhun et al, 2013; Lingle, Wyman, Kotrba, Teichroeb, & Romanow, 2012; Parga et al, 2020; Wasz-Höckert, Michelsson, & Lind, 1985).…”
Section: Discussionmentioning
confidence: 93%